Fire and desolation : the Revolutionary War's 1778 campaign as waged from Quebec and Niagara against the American frontiers - Watt, Gavin K (Dundurn, 2017)
"Following a disastrous campaign in 1777, the alliance between the Six Nations and the British Crown became seriously strained. Relations were made even more difficult by the hands-off stance of Quebec's governor, General Guy Carleton, which led to the Native leaders developing their own strategies and employing traditional tactics, leading to a ferocious series of attacks on the frontiers of Vermont, New York, and Pennsylvania, supported by Loyalist and Regular troops. Among these were two infamous actions, referred to as "massacres" by American historians--attacks on the Wyoming and Cherry Valleys. This destructive campaign prompted the Continental Congress to mount three major retributive expeditions against the territories of the Six Nations and their allies the following year. In Fire and Desolation, Gavin Watt details individual historical conflicts and illustrates the crushing tactical expertise of the Senecas and their American allies and provides a fresh perspective on Canada's involvement in the American Revolution and the unfolding events of 1778"--